2020
DOI: 10.22175/mmb.8759
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Normal and Woody Breast Meat from Broilers of Five Genetic Strains

Abstract: Woody breast (WB) is an emergent broiler myopathy that is macroscopically characterized by hardened areas of the Pectoralis major muscle. Five genetic strains (strains 1–5) of mixed-sex broilers were fed either a control or an amino acid (AA)-reduced diet (20% reduction of digestible lysine, total sulfur AAs, and threonine) for 8 wk. Differences between whole-muscle proteome profiles of normal breast (NB; n = 6 gels) and WB tissue (n = 6 gels) were characterized for (1) broiler strains 1–5 that were fed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…TRFE (TF), a transport protein, connects the two functional groups for muscle structure and carbohydrate metabolism. In our previous study, we found that TRFE was more abundant in WB than in NB at 24 h postmortem, indicating a stressed physiological condition in WB, according to a study conducted by Awad et al, whereas the decreased TRFE in postmortem WB may be a result of more drip loss due to the weakened protein structure. Because of the iron-binding ability, TRFE has an antibacterial effect, since iron is one of the essential nutrients for bacterial growth .…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…TRFE (TF), a transport protein, connects the two functional groups for muscle structure and carbohydrate metabolism. In our previous study, we found that TRFE was more abundant in WB than in NB at 24 h postmortem, indicating a stressed physiological condition in WB, according to a study conducted by Awad et al, whereas the decreased TRFE in postmortem WB may be a result of more drip loss due to the weakened protein structure. Because of the iron-binding ability, TRFE has an antibacterial effect, since iron is one of the essential nutrients for bacterial growth .…”
Section: Resultsmentioning
confidence: 52%
“…HSP27 degradation was positively correlated with protein degradation and meat tenderness. In our previous study on the proteomic differences between NB and WB, we found that HSP27 was more abundant in WB than in NB tissue postmortem, potentially due to a higher pH and greater oxidative stress. The extent of HSP27 decline postmortem was related to higher ultimate pH values, with higher values associated with higher levels of HSP27 .…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations